Language achievement predicts anxiety and not the other way around: A cross-lagged panel analysis approach - Alamer, Abdullah; Lee, Jihyun (Language teaching research : LTR, 2024)
While language anxiety is known to be a strong predictor of the second language (L2) achievement for decades, there has been a relative lack of empirical attention to establishing which one – anxiety or achievement – influences the other. The present study, based on a cross-lagged panel analysis, examined the causal relationships between language anxiety and L2 achievement, each of which was measured at three times points across 17 weeks. The results supported the directional relationship from L2 achievement at Time 2 to language anxiety at Time 3 while the opposite directional relationship from language anxiety at Time 2 to L2 achievement at Time 3 was not supported. Thus, our results suggest that language achievement precedes anxiety and not the other way round. The moderation analysis further sheds light on the importance of the earlier L2 achievement in the development of anxiety later on, by understanding learners’ motivational profiles. That is, learners with high autonomous motivation and high achievement at Time 1 exhibited a further decrease in anxiety at Time 3. On the other hand, learners with high autonomous motivation but low achievement showed a higher level of anxiety at Time 3. Overall, the present study makes a noteworthy contribution to one of the most debatable issues in the field and concludes with some practical implications for L2 educators.